Experimental Study on the Bearing Capacity of Glass Deck under the Condition of Vehicle Traffic - Peng Tang* (Tehnički Vjesnik, 2021)
In order to study the mechanical properties of the glass plate structure applied to the automobile bridge deck, the bearing capacity test of the glass bridge deck under the wheel load is carried out, and the failure mode, load displacement curve and safety function of the glass plate under the boundary, position and number of layers of the wheel load are analyzed. The results show that the ultimate bearing capacity of laminated glass under the condition of simply supported boundary on both sides is about four sides supported 71.8%. The ultimate bearing capacity of single-layer glass under the boundary condition of simple support on both sides is about four sides 51.4% from the point of view of meeting the structural strength requirements. The loading test is carried out by applying different multiple wheel loads at the plate angle and the center of the plate. The test results can provide reference for the application of the glass bridge deck in engineering.